Analisis Kalimat Simpleks Kompleks Pada Berita kompas.com - Adika Candra Putra; Bagas Beny Ardiyono; Gandi Noviyanto; Eva Dwi Kurniawan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Journalistic language plays an important role in conveying information concisely, clearly, and in a manner that is easily understood by readers. News headlines, as a primary element of journalistic texts, often employ specific sentence structures to condense information. This study aims to analyze the use of simplex and complex sentences in political news headlines on the Kompas.com website based on the rules of Tata Bahasa Baku Bahasa Indonesia (Standard Indonesian Grammar). The method used is descriptive qualitative, with data collection techniques consisting of observation and note-taking. The research data comprise 15 political news headlines published by Kompas.com within a certain time period. The results show that there are two types of sentences used in these headlines, namely simplex sentences and complex sentences. Complex sentences are found to be more dominant than simplex sentences, with a tendency toward the use of hypotactic and paratactic structures. The dominance of complex sentences indicates the media’s strategy in delivering political information in a concise and effective manner. Nevertheless, the use of sentence structures in news headlines must still adhere to linguistic rules in order to avoid ambiguity of meaning. This study is expected to contribute to research in Indonesian syntactic studies, particularly in the analysis of journalistic language.